The Effect of Adult Children's Education Attainment on Their Parents' Cognitive Health: An Intergenerational Support Perspective - Xu, Ying; Luo, Yaping (Frontiers in Public Health, 2022)
The purpose of this study is to examine the relationship between adult children’s education attainment and their parents’ cognitive health, and to further explore the mechanism of intergenerational support. Based on empirical analysis of data from China Health and Retirement Longitudinal Survey, our study finds a positive association between children's educational attainment and parents' cognitive health. This correlation is provided for by emotional communication of informal caregiving, financial support, and healthy behaviors shaped in the parents by adult children. The strength of the effect varied by the adult child’s gender. While sons’ education attainment significantly improves parental cognitive parameters through informal caregiving, financial support, and development of healthy behaviors, the effect of daughters’ education derives from financial support and healthy behaviors, not being related to informal caregiving. The study enriches the evidence on the mobility of children's human capital towards their parents and provides practical insights for advancing children's participation in family caregiving.